Snow flower and the secret fan : a novel - See, Lisa. (New York : Random House, 2006)
In nineteenth century China, in a remote Hunan county, a girl named Lily, at the tender age of seven, is paired with a laotong, or "old same," in an emotional match that will last a lifetime. The two women exchange messages written on silk fans and handkerchieves using nu shu, a unique language that women created in order to communicate in secret, sharing their experiences, but when a misunderstanding arises, their friendship threatens to tear apart.
Includes Reader's guide (p. 261-269)
Keywords: Reminiscing in old age -- Fiction; Female friendship -- Fiction; Women -- China -- Fiction; Married women -- Fiction; Older women -- Fiction; Footbinding -- Fiction; Childbirth -- Fiction; Secrecy -- Fiction; China -- Fiction; Psychological fiction; Domestic fiction